2007
DOI: 10.1007/s00442-007-0750-y
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove growth in New Zealand estuaries: the role of nutrient enrichment at sites with contrasting rates of sedimentation

Abstract: Mangrove forest coverage is increasing in the estuaries of the North Island of New Zealand, causing changes in estuarine ecosystem structure and function. Sedimentation and associated nutrient enrichment have been proposed to be factors leading to increases in mangrove cover, but the relative importance of each of these factors is unknown. We conducted a fertilization study in estuaries with different sedimentation histories in order to determine the role of nutrient enrichment in stimulating mangrove growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 42 publications
4
65
1
1
Order By: Relevance
“…Despite the importance of salinity control of the mangrove species distribution, we must consider the importance of many other physico-chemical factors (NICKERSON;THIBODEAU, 1985; FELLER et al, 2003;LOVELOCK et al, 2007), which and are also regulated by tidal flooding. The progressive decrease of structural development towards the transition zone between the forest and the salt flat observed in Guaratiba has also been reported previously for other dry or seasonally dry regions (BALL, 1980;SCHAEFFER-NOVELLI et al, 1990;CINTRON-MOLERO, 1993;SANTOS et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of salinity control of the mangrove species distribution, we must consider the importance of many other physico-chemical factors (NICKERSON;THIBODEAU, 1985; FELLER et al, 2003;LOVELOCK et al, 2007), which and are also regulated by tidal flooding. The progressive decrease of structural development towards the transition zone between the forest and the salt flat observed in Guaratiba has also been reported previously for other dry or seasonally dry regions (BALL, 1980;SCHAEFFER-NOVELLI et al, 1990;CINTRON-MOLERO, 1993;SANTOS et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Both periods coincided with periods of sustained El Niño activity, an atmospheric phenomenon highly influenced by global climate change. Another study from Lovelock et al (2007) showed that, in two other estuaries in New Zealand, fertilization and high sedimentation rate, probably induced by stronger El Niño, favored mangrove area increase. Stokes et al (2010) carried out a study in two embayments of Tauranga Harbour in New Zealand and found that spreading mangroves had become a coastal management issue even under a temperate climate environment.…”
mentioning
confidence: 99%
“…The poor relationship between above and below-ground biomass and C stocks in our study may be associated with a shift in biomass partitioning due to environmental conditions (McKee, 1995;Pezeshki et al, 1997;Naidoo, 2009;Alongi, 2011;Castañeda-Moya et al, 2013). For example, factors such as low sedimentation (Lovelock et al, 2007), high salinity (Saintilan, 1997b;Ball, 1998), extreme weather events (Osland et al, 2014), light limitation (McKee, 1995), and increased water depth or flooding (Ye et al, 2003) have been linked to low above-ground biomass in mangrove. Mangroves have also been shown to allocate more biomass below-ground due to nutrient limitation (McKee, 1995;Naidoo, 2009;Alongi, 2011), low soil redox conditions (Pezeshki et al, 1997), high sulfide concentrations, and permanent flooding (Castañeda-Moya et al, 2013).…”
Section: Below-ground Biomass and Allometry Of Temperate A Marina Fomentioning
confidence: 69%